2009
DOI: 10.1158/0008-5472.can-08-3873
|View full text |Cite
|
Sign up to set email alerts
|

Human Bone Marrow–Derived Mesenchymal Stem Cells for Intravascular Delivery of Oncolytic Adenovirus Δ24-RGD to Human Gliomas

Abstract: AbstractΔ24-RGD is an infectivity-augmented, conditionally replicative oncolytic adenovirus with significant antiglioma effects. Although intratumoral delivery of Δ24-RGD may be effective, intravascular delivery would improve successful application in humans. Due to their tumor tropic properties, we hypothesized that human mesenchymal stem cells (hMSC) could be harnessed as intravascular delivery vehicles of Δ24-RGD to human gliomas. To assess cellular events, green fluorescent protein-labeled hMSCs carrying Δ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
179
0
6

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(188 citation statements)
references
References 37 publications
3
179
0
6
Order By: Relevance
“…After intravascular administration, MSCs loaded with Ad-Δ24RGD, but not Ad-Δ24-RGD alone, migrated to and infected intracerebral gliomas, resulting in a significant increase in survival. 113 When compared directly, both human MSCs and NSCs loaded with CRAd-S-pk7 (Table I) supported Ad replication and migration to tumors, however, loaded NSCs were significantly better than MSCs in extending survival. 111 Additional studies with CRAd-S-pk7 loaded HB1.F3 NSCs, which are currently in clinical trial, demonstrated that the infected NSCs retained their tumor homing, supported Ad replication, and gave rise to infected tumor cells in vivo.…”
Section: Stem Cells As Oncolytic Virus Carriersmentioning
confidence: 98%
See 1 more Smart Citation
“…After intravascular administration, MSCs loaded with Ad-Δ24RGD, but not Ad-Δ24-RGD alone, migrated to and infected intracerebral gliomas, resulting in a significant increase in survival. 113 When compared directly, both human MSCs and NSCs loaded with CRAd-S-pk7 (Table I) supported Ad replication and migration to tumors, however, loaded NSCs were significantly better than MSCs in extending survival. 111 Additional studies with CRAd-S-pk7 loaded HB1.F3 NSCs, which are currently in clinical trial, demonstrated that the infected NSCs retained their tumor homing, supported Ad replication, and gave rise to infected tumor cells in vivo.…”
Section: Stem Cells As Oncolytic Virus Carriersmentioning
confidence: 98%
“…110 Several groups have demonstrated that MSCs and NSCs can support Ad infection and replication. [111][112][113][114] An advantage of this approach to oncolytic virus alone is that stem cells can be delivered intravascularly, evading anti-viral immunity, and then extravasate into the brain, or intracranially at a distance from the tumor. After intravascular administration, MSCs loaded with Ad-Δ24RGD, but not Ad-Δ24-RGD alone, migrated to and infected intracerebral gliomas, resulting in a significant increase in survival.…”
Section: Stem Cells As Oncolytic Virus Carriersmentioning
confidence: 99%
“…Investigators have demonstrated the in vivo migratory capacity of stem cells toward primary GBM tumors as well as invasive tumor cells that intermingle with normal brain tissue (19)(20)(21)(22)(23)(24)(25)(26)(27)(28). Various stem cells such as embryonic stem cells, mesenchymal stem cells, neural stem cells, induced pluripotent stem cells (iPSCs), and neural stem cells derived from iPSCs have been shown to migrate to intracranially established GBMs when implanted loco-regionally within the brain, and their ability to secrete anti-GBM therapies after genetic modification has been investigated (29).…”
Section: Controllable Drug Delivery Using Stem Cells In Conjunction Wmentioning
confidence: 99%
“…Mesenchymal stromal cells loaded with Ad-D24RGD have been able to migrate to and infect intracerebral gliomas, whereas Ad-D24RGD alone was unable to do so. 87 …”
Section: Gene Therapy For Brain Tumorsmentioning
confidence: 99%